Depression, anxiety, and stress among adolescents in Kuantan and its association with religiosity- a pilot study - Mohamad, Ahmad Safwan; Draman, Samsul; Md Aris, Mohd Aznan; Musa, Ramli; Mohd Rus, Razman; Malik, Maszlee (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Adolescence is a period of time when the development of personality and psychology is taking place. Studies have shown that religiosity can affect the mental health of a person. Many tools have been developed to assess religiosity of a person; one of them is the Santa Clara Strength of Religious Faith (SCSORF) scale. In this study, a translation and validation for SCSORF Malay Version (SCSORF-M) is done, and subsequently used to look for the association between religiosity and mental health in adolescents. Fifty questionnaire papers have been distributed to 50 students in secondary schools in district of Kuantan. The mean score for depression, anxiety, and stress are 5.83, 5.59, and 8.34 respectively. Only 10 (24.4%) have no depression, 9 (22%) have no anxiety, and 13 (31.7%) have no stress. The mean score for SCSORF-M scale was 35.3 (range 25-40). Family income has shown to correspond negatively with the depression, anxiety, and stress, while religiosity has shown to be correlating negatively with depression and stress, but positive correlation with anxiety. SCSORF-M has positive convergent correlation with Duke’s University Religiosity Index Malay Version (DUREL-M) in all domains. SCSORF-M has shown good Cronbach’s alpha value (0.84). In conclusion, religiosity is an important factor to contribute to the outcome of mental health among adolescents. SCSORF-M can be used as an assessment tool for religiosity.